1982
DOI: 10.1016/0277-5379(82)90007-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of carminomycin and carminomycinol in man, measured by high pressure liquid chromatography

Abstract: In 9 patients with advanced malignant disease who received carminomycin (CMM) in an i.v. bolus injection (dose 18 mg/m2), curves of plasma concentrations of CMM and carminomycinol (CMMOH), a metabolite, versus time were constructed. For determination of plasma concentrations, high pressure liquid chromatography was used. For CMM and CMMOH the median areas under the curves (AUC's) were 31 (range 4-57) X 10(-8) mol/Ql/hr (measured over 24 hr) and 100 (range 309-158) X 10(-8) mol/l/hr (measured over 48 hr) respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
1985
1985

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Plasma samples were extracted according to a modification of a procedure developed for carminomycin (CMM) (8). To one ml plasma samples carminomycin was added as internal standard (50 or 250 ng/ml), to correct for differences in extraction efficiency.…”
Section: Sample Clean-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma samples were extracted according to a modification of a procedure developed for carminomycin (CMM) (8). To one ml plasma samples carminomycin was added as internal standard (50 or 250 ng/ml), to correct for differences in extraction efficiency.…”
Section: Sample Clean-upmentioning
confidence: 99%
“…Aqueous solutions of 4'-epi-DX and carminomycin (CMM) are unstable due to light and temperature influences which have been previously described for other anthracyclines (8,9). 4'-Epi-DX and CMM declined to 57% and 28% of the initial concentration (1.8 • 10-4M) respectively after 20 h at 25~ under daylight.…”
Section: Stability Of Solutionsmentioning
confidence: 99%
“…Therefore, it appears that the metabolism of esorubicin is limited. In contrast, with other anthracycline derivatives such as daunorubicin and daunorubicin analogs, the formation of alcohol derivatives is much more pronounced (22)(23)(24). Variations in the production of alcohol derivatives are related to the ability of these antbracycline antibiotics to function as substrates for the aldoketoreductase (25).…”
Section: Discussionmentioning
confidence: 99%
“…As compared to doxorubicin, it exerts a 10 to 100 times greater inhibitory effect in vitro against normal human marrow myeloid colony-forming cells (4,5). Clinical pharmacology studies indicate that peak plasma levels average 0.05 #g/ml with areas under the plasma concentration vs. time curves varying between 4 and 57 • 10 -8 M/1/h (4,6). Initial clinical studies yielded promising therapeutic results in various malignancies (7,8), but recent EORTC trials revealed lack of drug activity in breast cancer and soft tissue sarcoma (9,10).…”
Section: Introductionmentioning
confidence: 99%